Plant Stand And Stability increment Sengon (Albizia falcataria) in Sub Lempake District of North Samarinda - Rahman, Taufik; Jumani, Jumani; Emawati, Heni (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The purpose of this study was to determine or calculate the increment of diameter at breast height and increment of total height and stability of standing crops Sengon (Albizia falcataria) contained in the study site, to determine whether or not the activities thinning done on plants Sengon (Albizia falcataria) contained in the study site and to recommend spacing especially on the reforestation or afforestation activities that planting of this type.Becoming object in this research is a plant Sengon (Albizia falcataria) contained in these locations. Based on the results of a discussion with Mr. Jamal as the owner of the land and plant Sengon (Albizia falcataria), cultivated land Sengon (Albizia falcataria) approximately 0.5 hectares, the number of plants and more than 220 plants were planted in 2007 so that the age of the plant at the time this research was done approximately 9 years. While a spacing based on direct measurements at the study site approximately 3 m x 3 m.The number of plant samples Sengon (Albizia falcataria) taken with a sampling intensity by 25% thus totaling 55 plants and selected intentionally (purposive sampling).Based on the results of the measurement and the calculation of the diameter at breast height and the total height of the plant Sengon (Albizia falcataria) at the time of this study made at the time the plant was 9 years gained an average diameter at breast height of 23.79 cm, the average height of a total of 13 , 56 m, the average increment at breast height diameter of 2.64 cm / plant / year, the average increment of the total height of 1.51 m / plant / year and stability stands at 57.00.